2017
DOI: 10.1186/s13012-017-0650-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing evidence-based diabetes and chronic disease control among local health departments: a multi-phase dissemination study with a stepped-wedge cluster randomized trial component

Abstract: BackgroundThe rates of diabetes and prediabetes in the USA are growing, significantly impacting the quality and length of life of those diagnosed and financially burdening society. Premature death and disability can be prevented through implementation of evidence-based programs and policies (EBPPs). Local health departments (LHDs) are uniquely positioned to implement diabetes control EBPPs because of their knowledge of, and focus on, community-level needs, contexts, and resources. There is a significant gap, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 81 publications
0
32
0
Order By: Relevance
“…This national cross-sectional study was part of a larger study that used a stratified random sampling design to invite one individual from each included US LHD to complete an online survey [41]. Eligible LHDs were those that screened for diabetes or body mass index, or conducted or contracted for population-based nutrition and physical activity efforts, according to the 2016 National Association of County and City Health Officials (NACCHO) National Profile survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This national cross-sectional study was part of a larger study that used a stratified random sampling design to invite one individual from each included US LHD to complete an online survey [41]. Eligible LHDs were those that screened for diabetes or body mass index, or conducted or contracted for population-based nutrition and physical activity efforts, according to the 2016 National Association of County and City Health Officials (NACCHO) National Profile survey.…”
Section: Methodsmentioning
confidence: 99%
“…The survey included sections on mis-implementation (frequency and reasons), LHD and participant characteristics, skills for EBDM, and organizational supports. After three rounds of study team input and cognitive response testing with 10 chronic disease prevention practitioners, the survey demonstrated acceptable test-retest reliability [41].…”
Section: Survey Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…14 A scoping review by Wilson et al 15 identified that the steps in KT frameworks relating to adapting knowledge to the local context, assessing barriers to knowledge use and implementing interventions to promote knowledge use (referred to as dissemination in his review) were generally underpinned by at least one of the following theories: persuasive communication, diffusion of innovations theory or social marketing. Parks et al 16 provide a detailed methodology for enhancing the dissemination and update of programs and policies to enhance diabetes-related care in local health departments using some of these frameworks. Kastner and Straus illustrate how the knowledge to action framework was used to create a clinical support tool to enhance osteoporosis disease management by primary care providers.…”
mentioning
confidence: 99%
“…The efficient global prevention and control of chronic disease has gradually become a focus for scholars [1][2]. Evidence-based chronic disease prevention (EBCDP) has emerged and become popularized as a scientific tool to increase the efficiency of preventing and controlling diseases in developed countries [3].…”
Section: Introductionmentioning
confidence: 99%